Murine globoid cell leukodystrophy (the twitcher mouse). The presence of characteristic inclusions in the kidney and lymph nodes. - Takahashi, H. (1983)
Ultrastructural investigations were carried out on the kidney, lung, liver, spleen, lymph nodes and adrenal gland of the twitcher mouse, a recently discovered authentic murine model of human globoid cell leukodystrophy (GLD). The characteristic cytoplasmic inclusions identical to those found in the glial and globoid cells in the central nervous system (CNS) were observed in the epithelial cells of the thin limbs of the loops of Henle in the kidney and also in the macrophages in the lymph nodes. Such inclusions were not detected in the systemic organs in a case of human GLD. This fact may indicate an important species difference between the human and murine forms of GLD, although the genetic enzymatic defect is the same.